Looking into the future Evangelical studies in eschatology - Baker, David Weston, 1950-; Evangelical Theolgical Society. Meeting (1999). (Grand Rapids, MI Baker Academic, 2001)
Includes bibliographical references and index.
Papers from the 1999 Annual Meeting of the Evangelical Theological Society.
Keywords: Eschatology; Evangelicalism